Berkebun Hidroponik untuk Ketahanan Pangan Selama Pandemi Covid-19 di Perum Cepu Asri Blora - Herraprastanti, Eva Hertnacahyani; Korawan, Agus Dwi; Suprawikno, Suprawikno (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
This Community Partnership Program (PKM) was implemented as an effort to restore the economy of the people affected by Covid-19, namely in Cepu Asri Housing, Blora Regency. Covid-affected families must continue to have their food needs fulfilled during the independent isolation period. One way to do this is to take advantage of the narrow land of the house yard with hydroponic gardening. The solution offered to partners was to make shelves for growing vegetables and provide training in farming. In order for the PKM program to be achieved according to the target, this activity emphasized the active participation of partners, while the Abdi team from STTR Cepu was only as technical assistance. Active participation of partners in the form of planning activities, purchasing media and hydroponic installation tools, scheduling and conducting activities. The active participation of these partners has an impact on the independence of the partners in terms of designing, managing and developing activities even though PKM activities have ended. At the end of the PKM implementation, an evaluation was carried out by the Abdi STTR Cepu team which was useful in developing further activities. The resulting output was that the partners obtained knowledge about assembling hydroponic system gardening installations, and partners obtained fresh vegetables that could be harvested at any time as needed, which could be used. alone or sold so that it can help save family finances.